2021
DOI: 10.3389/fneur.2021.760855
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Economic Outcomes of Intravenous Brivaracetam Compared With Levetiracetam for the Treatment of Seizures in United States Hospitals

Abstract: Background: Seizures are common among hospitalized patients. Levetiracetam (LEV), a synaptic vesicle protein 2A (SV2A) ligand, is a common intravenous (IV) anti-seizure medication option in hospitals. Brivaracetam (BRV), a selective SV2A ligand for treatment of focal seizures in patients ≥16 years, has greater binding affinity, higher lipophilicity, and faster brain entry than IV LEV. Differences in clinical outcomes and associated costs between IV BRV and IV LEV in treating hospitalized patients with seizure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…A retrospective cohort analysis of real-world chargemaster data from 860 United States hospitals in the Premier Healthcare Database was conducted in adult patients treated with IV LEV (n = 360) or IV BRV (n = 90) for seizures within the hospital setting. 57 Patients treated with IV BRV had a lower prevalence of ICU admission than patients treated with IV LEV (14.4% vs. 24.2%; P <.05), as well as lower 30-day seizure-related readmissions (0% vs. 4.2%; P <.05), and adjusted odds for ICU admission was 47% lower for patients treated with IV BRV versus IV LEV ( P <.05). These findings are associations and not evidence of causality, as the order of events could not be determined from the hospital billing data.…”
Section: Resultsmentioning
confidence: 88%
“…A retrospective cohort analysis of real-world chargemaster data from 860 United States hospitals in the Premier Healthcare Database was conducted in adult patients treated with IV LEV (n = 360) or IV BRV (n = 90) for seizures within the hospital setting. 57 Patients treated with IV BRV had a lower prevalence of ICU admission than patients treated with IV LEV (14.4% vs. 24.2%; P <.05), as well as lower 30-day seizure-related readmissions (0% vs. 4.2%; P <.05), and adjusted odds for ICU admission was 47% lower for patients treated with IV BRV versus IV LEV ( P <.05). These findings are associations and not evidence of causality, as the order of events could not be determined from the hospital billing data.…”
Section: Resultsmentioning
confidence: 88%
“…A metaanalysis of randomized controlled studies by Zhang et al, comprising 1876 patients using levetiracetam and brivaracetam, found that LEV may be more effective than brivaracetam while having a reduced risk of dizziness [32]. Contrarily, Beaty et al, reported that due to decreased or equivalent rates of ICU admission, intubation, and 30-day seizure-related readmission, intravenous (IV) brivaracetam may offer an option to IV levetiracetam for the treatment of seizures in the hospital environment [33].…”
Section: Discussionmentioning
confidence: 99%